Augmented Input Reveals Word Deafness in a Man with Frontotemporal Dementia - Chris Gibbons; Barry Oken; Melanie Fried-Oken (Behavioural Neurology)
We describe a 57 year old, right handed, English speaking man initially diagnosed with progressive aphasia. Language assessment revealed inconsistent performance in key areas. Expressive language was reduced to a few short, perseverative phrases. Speech was severely apraxic. Primary modes of communication included gesture, pointing, gaze, physical touch and leading. Responses were 100% accurate when he was provided with written words, with random or inaccurate responses for strictly auditory/verbal input. When instructions to subsequent neuropsychological tests were written instead of spoken, performance improved markedly. A comprehensive audiology assessment revealed no hearing impairment. Neuroimaging was unremarkable. Neurobehavioral evaluation utilizing written input led to diagnoses of word deafness and frontotemporal dementia, resulting in very different management. We highlight the need for alternative modes of language input for assessment and treatment of patients with language comprehension symptoms.